Autodidactic English Learning Strategy of Tour Guide in the Raja Ampat Island - Marlontinus Wair; Nursalim; Rizqi Claudia Wardani. H (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores the autodidactic English learning strategies employed by local tour guides in Raja Ampat Island, a prominent marine tourism destination in eastern Indonesia. Due to limited access to formal language education, many guides independently develop their English skills to meet the communication demands of international tourism. Adopting a mixed-methods approach, the study involved 10 participants through in-depth interviews and a structured questionnaire. Thematic analysis was used to interpret qualitative data, while descriptive statistics supported the quantitative insights. The findings reveal that tour guides employ diverse self-directed strategies, including setting personal learning goals, practicing English through direct interactions with tourists, mimicking native speakers, maintaining vocabulary notebooks, and using digital tools such as Google Translate, YouTube, and ELSA Speak. These strategies align with theoretical frameworks such as Heutagogy, Self-Directed Learning (SDL), and Constructivism. Among the most effective approaches was real-time communication with international visitors, offering authentic exposure and immediate language application. Despite their dedication, participants reported several challenges, including limited grammar knowledge, lack of corrective feedback, and irregular learning routines. However, their strong intrinsic motivation, adaptability, and problem-solving attitudes illustrate the potential of self-managed learning in remote areas. The study concludes that autodidactic learning can be a viable path for language development in tourism sectors where formal instruction is scarce. It also suggests the need for accessible digital resources and minimal structured support to optimize learning outcomes. These findings offer practical implications for language educators, tourism authorities, and policymakers interested in enhancing the communicative competence of tour guides in under-resourced regions.